A New Role for SAG12 Cysteine Protease in Roots of Arabidopsis thaliana - James, Maxence; Masclaux-Daubresse, Céline; Marmagne, Anne; Azzopardi, Marianne; Laîné, Philippe; Goux, Didier; Etienne, Philippe; Trouverie, Jacques (Frontiers in Plant Science, 2019)
Senescence associated gene (SAG) 12, which encodes a cysteine protease is considered to be important in nitrogen (N) allocation to Arabidopsis thaliana seeds. A decrease in the yield and N content of the seeds was observed in the Arabidopsis SAG12 knockout mutants (sag12) relative to the wild type (Col0) under limited nitrogen nutrition. However, leaf senescence was similar in both lines. To test whether SAG12 is involved in N remobilization from organs other than the leaves, we tested whether root N could be used in N mobilization to the seeds. Root architecture, N uptake capacity and 15N partitioning were compared in the wild type and sag12 under either high nitrogen (HN) or low nitrogen (LN) conditions. No differences in root architecture or root N uptake capacity were observed between the lines under HN or LN. However, under LN conditions, there was an accumulation of 15N in the sag12 roots compared to the wild type with lower allocation of 15N to the seeds. This was accompanied by an increase in root N protein contents and a significant decrease in root cysteine protease activity. SAG12 is expressed in the root stele of the plants at the reproductive stage, particularly under conditions of LN nutrition. Taken together, these results suggest a new role for SAG12. This cysteine protease plays a crucial role in root N remobilization that ensures seed filling and sustains yields when nitrogen availability is low.